PERANCANGAN HMI (HUMAN MACHINE INTERFACE) SEBAGAI PENGONTROL DAN PENDETEKSI DINI KERUSAKAN KAPASITOR BANK BERBASIS PLC - Bukit, Ferry Rahmat Astianta; Syahputra, Kurnia Agung; Suherman, Suherman (Teknik Elektro Universitas Siliwangi, 2022)
Progammable Logic Controller (PLC) is a user friendly, microprocessor-based equipment that contains control functions of various types and levels of complexity. The control system is designed to be able to monitor the value of the power factor to remain stable and can determine the indication of early damage to the capacitor bank. In this research, an automatic control system is designed that can turn on the capacitor bank when the power factor value ≤ 0.95 and turn off the capacitor bank when the power factor value ≥1. HMI can provide data indication of early breakdown of capacitor banks based on the current value of each capacitor. This system utilizes PLC GE, and CE Digital Transducer so that the condition of the capacitor bank can be known in case of damage and decreased efficiency. Based on the test, when the power factor value is 0.95, the program will turn on the capacitor bank to meet the set point value of 0.95 and turn on the alarm indication that the power factor value is not sufficient, when the power factor value exceeds ≥1, the program will turn off the capacitor bank that works longer. The HMI system is able to provide data to perform preventive maintenance activities on a regular basis in order to maintain the efficiency and reliability of capacitor banks.